2020
DOI: 10.1002/jdd.12459
|View full text |Cite
|
Sign up to set email alerts
|

Australian dental practitioner perspectives on academic careers

Abstract: Objectives Due to forecasted faculty shortages and increasing student enrollments in dental education, there is a need to attract talented clinicians into academia. To address this growing concern, we need to explore dental practitioners’ perspectives on the academic career pathway, including enablers and barriers to entering the academic workforce. Methods A mixed‐methods electronic survey was disseminated through professional associations and dental groups on social media in 2018. Qualitative responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Academic dentistry is infrequently a career goal for dental students or practicing dentists, and there are limited pathways for new graduates into the dental school faculty. 32,33 Although half of dental graduates express interest in working in dental education, less than one percent intend to do so immediately following graduation. 34 Concerns around income and indebtedness are two of the most important factors preventing new graduates from pursing academic careers.…”
Section: Faculty Pipeline Programsmentioning
confidence: 99%
“…Academic dentistry is infrequently a career goal for dental students or practicing dentists, and there are limited pathways for new graduates into the dental school faculty. 32,33 Although half of dental graduates express interest in working in dental education, less than one percent intend to do so immediately following graduation. 34 Concerns around income and indebtedness are two of the most important factors preventing new graduates from pursing academic careers.…”
Section: Faculty Pipeline Programsmentioning
confidence: 99%
“…Research with dentistry clinicians has also identified lack of career development as a source of occupational stress 10 . It has been previously reported that whilst a career in dentistry academia is well regarded, the possibilities for pursuing this career are unclear to dentistry clinicians and students 39 . Previous research has identified that most current dentistry academics have no formal training in education or knowledge of pedagogy which can hinder career development in the profession 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that whilst a career in dentistry academia is well regarded, the possibilities for pursuing this career are unclear to dentistry clinicians and students 39 . Previous research has identified that most current dentistry academics have no formal training in education or knowledge of pedagogy which can hinder career development in the profession 39 . This may, however, change with universities offering career development and leadership training to academic staff 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor financial reward, geographical location of universities, lack of educational training, loss of clinical skills, and lack of a clear career pathway were the main drawbacks reported by dentists practicing in private settings. 7,8 The income discrepancy between academic dentistry and private practice has been highlighted as the first major barrier. 9 Student indebtedness is another significant driver influencing the career decisions of recent dental and residency graduates.…”
Section: Barriers To a Career In Academiamentioning
confidence: 99%